Guardare i sex robots attraverso le lenti femministe - Rigotti, Carlotta (Filosofia, 2020)
Since the 1970s, feminisms have stressed the intersection between gender and technology. Yet, while being mainly focused on the female access to technology, reproductive technologies and a cyborg future, no feminist narrative has ever addressed the ongoing robotic revolution and its relating challenges to the notion of gender, as in the case of sex robots. Shaped as humans and endowed with basic AI capabilities, sex robots are machines programmed to provide sexual performances; their stereotypical shape and behaviour, though, raise questions on their potential to perpetuate gender inequality. Therefore, this paper seeks to assess female sex robots through feminist lens and to repurpose them as a feminist technology.